2015
DOI: 10.3892/or.2015.4206
|View full text |Cite
|
Sign up to set email alerts
|

miR-1291 targets mucin 1 inhibiting cell proliferation and invasion to promote cell apoptosis in esophageal squamous cell carcinoma

Abstract: Abstract. MicroRNAs (miRNAs) are well known as important regulators in various cancer development. In the present study, we focused on the expression and biological function of miR-1291 in esophageal squamous cell carcinoma (ESCC). Compared with adjacent non-tumorous tissue samples, qRT-PCR data showed significant downregulation of miR-1291 in 54 ESCC tissue samples (P<0.05), which was also significantly associated with lymph node metastases and clinical stage (P<0.05). Cell Counting Kit-8 (CCK-8), colony form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
7
30
0
Order By: Relevance
“…This study design is distinguished from our recent report that involves the use of different mice for xenograft tumor study [32], and current tumor mouse model not only allows the reduction of number of experimental animals for research but also minimizes interindividual variability and other confounding factors. Nevertheless, consistent results are obtained from present and previous studies [31, 32, 34, 42], indicating that miR-1291 acts as a tumor suppressor in renal, esophageal squamous, and pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study design is distinguished from our recent report that involves the use of different mice for xenograft tumor study [32], and current tumor mouse model not only allows the reduction of number of experimental animals for research but also minimizes interindividual variability and other confounding factors. Nevertheless, consistent results are obtained from present and previous studies [31, 32, 34, 42], indicating that miR-1291 acts as a tumor suppressor in renal, esophageal squamous, and pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have showed that miR-1291 level is lower in renal cell carcinoma specimens [33] and esophageal squamous cell carcinoma [42], and restoration of miR-1291 suppresses renal and esophageal squamous cancer cell proliferation, migration and invasion [34, 42]. The present study is the first to find that miR-1291 is significantly downregulated in patient pancreatic carcinoma tissues and pancreatic cancer cell lines.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…On the other hand, we found eight down-regulated miRNAs, some of them implicated in multiple processes such as cancer ( miR20b-5p , miR-1291 ) 52, 53 , organ injury in toxicity drug models ( miR-382-5p ) 54 , metabolic processes and steroidogenesis ( miR-378b ) 55 , and tissue inflammation ( miR-3085-3p ) 56 . None of them has been studied in the context of testes physiology.…”
Section: Discussionmentioning
confidence: 91%
“…miR-3653 is upregulated in cervical cancer tissues associated with human papillomavirus (HPV) infection as compared with paired normal tissues 25 . miR-1291 promotes apoptosis in esophageal squamous cell carcinoma by targeting mucin1 26 . Third, these six miRNAs were detected in a panel of 5-FU-resistant colon cancer cell lines by qRT-PCR to identify chemoresistance-related miRNAs.…”
Section: Discussionmentioning
confidence: 99%